Two novel isostructural and heteroleptic Nd(III) and Dy(III)-organic frameworks constructed by 2, 5-pyridinedicarboxylic acid and in situ generated 2-pyridinecarboxylic acid: Hydrothermal synthesis, characterization, photoluminescence properties and heterogeneous catalytic activities. (7th July 2017) - Ay, Burak; Yildiz, Emel; Kani, İbrahim
Graphical abstract: Two novel 3D lanthanide-organic frameworks have been synthesized under hydrothermal conditions. The catalytic performances of MOFs were investigated and their selectivities were measured as 100% for the oxidation of thymol to thymoquinone. The photoluminescence properties of the MOFs have also been examined. Abstract: The crystal structures, heterogeneous catalytic activities and photoluminescent properties of two novel three dimensional (3D) metal organic frameworks (MOFs), [Nd(pyc)(pydc)(H2 O)] n (1 ) and [Dy(pyc)(pydc)(H2 O)] n (2 ) (H2 pydc = pyridine-2, 5-dicarboxylic acid, Hpyc = 2-pyridinecarboxylic acid) are presented. The synthesized complexes under hydrothermal conditions were characterized by the elemental analysis, inductively coupled plasma (ICP), fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), single crystal X-ray diffraction and powder X-ray diffraction (PXRD) analysis. For morphological analysis, field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) were used. The compounds are isostructural and each Ln 3+ (Nd(III) and Dy(III)) centers are eight-coordinated. MOFs have the distinct 3D open-framework architectures due to the presence of Hpyc ligands, which are converted from H2 pydc ligands in-situ decarboxylation under the hydrothermal conditions. Photoluminescence properties and thermal stabilities of the compounds have been investigated. Their heterogeneous catalytic activities have also been examined on the oxidation of the thymol (T) to thymoquinone (TQ). The structures of the MOFs were stable after three catalytic cycles. The maximum T conversion values, 40.37% and 36.45% were recorded with nearly 100% selectivities by using1 and2, respectively.